Rankl Impairs Lactogenic Differentiation Through Inhibition of the Prolactin/Stat5 Pathway at Midgestation. (13th January 2016) - Cordero, Alex; Pellegrini, Pasquale; Sanz‐Moreno, Adrián; Trinidad, Eva M.; Serra‐Musach, Jordi; Deshpande, Chetan; Dougall, William C.; Pujana, Miguel Angel; González‐Suárez, Eva
Abstract: Prolactin and progesterone both orchestrate the proliferation and differentiation of the mammary gland during gestation. Differentiation of milk secreting alveoli depends on the presence of prolactin receptor, the downstream Jak2‐Stat5 pathway and the transcription factor Elf5. A strict regulation of Rank signaling is essential for the differentiation of the mammary gland and in particular for alveolar commitment. Impaired alveologenesis and lactation failure are observed in both, knockout and Rank overexpressing mice; however, the underlying molecular mechanism responsible for these phenotypes remains largely unknown. Using genome‐wide expression analyses and functional studies, we show here that Rankl (RL) exposure leads to impaired secretory differentiation of alveolar cells not only in MMTV‐RANK but also in wild‐type (WT) mammary acini. Conversely, pharmacological blockage of Rank signaling at midgestation in WT mice leads to precocious and exacerbated lactogenesis. Mechanistically, RL negatively regulates Stat5 phosphorylation and Elf5 expression at the onset of lactogenesis. Continuous RL exposure leads to the expansion of basal and bipotent cells in WT and MMTV‐RANK acini. Overall, we demonstrate that enhanced Rank signaling impairs secretory differentiation during pregnancy by inhibition of the prolactin/p‐Stat5 pathway. Stem Cells 2016;34:1027–1039 Abstract :